Why Most Children Think Well of Themselves. Issue 6 (21st August 2017) - Thomaes, Sander; Brummelman, Eddie; Sedikides, Constantine
Abstract : This research aimed to examine whether and why children hold favorable self‐conceptions (total N  =   882 Dutch children, ages 8–12). Surveys (Studies 1–2) showed that children report strongly favorable self‐conceptions. For example, when describing themselves on an open‐ended measure, children mainly provided positive self‐conceptions—about four times more than neutral self‐conceptions, and about 11 times more than negative self‐conceptions. Experiments (Studies 3–4) demonstrated that children report favorable self‐conceptions, in part, to live up to social norms idealizing such self‐conceptions, and to avoid seeing or presenting themselves negatively. These findings advance understanding of the developing self‐concept and its valence: In middle and late childhood, children's self‐conceptions are robustly favorable and influenced by both external (social norms) and internal (self‐motives) forces. Abstract : The title for this Special Section isOrigins of Children's Self‐Views, edited by Eddie Brummelman and Sander Thomaes